Band gap tailoring of flower-like rutile-phased TiO2 nanostructured film grown via facile hydrothermal doping process for photocatalytic degradation of methylene blue - Abd Hamed, Noor Kamalia (2021)
One of the major drawback of TiO2 is its band gap. Among other approaches, doping process can be considered as one of the best options. However the current method in doping process has multiple and complex preparation steps that prolong the time for sample fabrication. Here, this study aimed to dope the rutile-phased TiO2 film with silver (Ag) and nitrogen (N) by using facile hydrothermal method to shorten the preparation time of doping process to reduce the band gap of TiO2. In this study, the film was produced by using facile hydrothermal method conducted at 150 °C for 10 hours. The ability of Ag and N element in reducing the band gap is well established. Thus, these dopants were used in facile hydrothermal method to investigate the ability of this method in tailoring the band gap. For Ag-doped TiO2, X-ray photoelectron spectroscopy (XPS) showed that the amount of Ti3+ -oxygen vacancy defects amplified after doping, whereas transmission electron microscopy (TEM) discovered that (110) and (111) facets were the exceptionally exposed facets. Conversely, for N-doped TiO2, XPS discovered that the amount of Ti3+ -oxygen vacancy defects reduced after doping, while TEM showed that the (101) and (111) facets were exceptionally exposed facets. The band gap energy was successfully reduced via this method. The band gap energy for undoped TiO2 film is 3.21 eV and after doping process with Ag and N element, the band gap value was reduced to 3.12 and 3.16, respectively. The Ag-FR TiO2 film doped with 1wt% Ag showed maximum degradation of methylene blue with 20% higher degradation as compared with the undoped TiO2. N-FR TiO2 2.0 wt% showed only a 6% increase in the photodegradation of methylene blue. The Ag doped TiO2 displayed the best photocatalytic activity compared to N doped TiO2. The effect of the synergy between the (110) and (111) facets, together with the Ti3+ -oxygen vacancy from the doped Ag, played a crucial role in decreasing the band gap as well as acting as electron traps to inhibit electrons and holes recombination, which prolonged the life of the photogenerated holes and electrons, thus enhancing the photocatalytic activity